2009
DOI: 10.3390/ijerph6082139
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Consumption by Wistar Rat Dams Affects Selenium Bioavailability and Antioxidant Balance in Their Progeny

Abstract: Ethanol consumption affects maternal nutrition, the mothers’ antioxidant balance and the future health of their progeny. Selenium (Se) is a trace element cofactor of the enzyme glutathione peroxidase (GPx). We will study the effect of ethanol on Se bioavailability in dams and in their progeny. We have used three experimental groups of dams: control, chronic ethanol and pair-fed; and three groups of pups. Se levels were measured by graphite-furnace atomic absorption spectrometry. Serum and hepatic GPx activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
2
14
0
2
Order By: Relevance
“…Moreover, our results indicated that Se is related to a high number of transport proteins for Se-Methionine (Se-Met) in the duodenum [14]. As we have previously reported, exposure of pups to ethanol during gestation and lactation causes an imbalance of Se homeostasis and a depletion in Se tissue deposits related to protein and lipid oxidation [15]. In order to improve our knowledge about the effects of ethanol on Se bioavailability in pups, we will study duodenal Se absorption.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, our results indicated that Se is related to a high number of transport proteins for Se-Methionine (Se-Met) in the duodenum [14]. As we have previously reported, exposure of pups to ethanol during gestation and lactation causes an imbalance of Se homeostasis and a depletion in Se tissue deposits related to protein and lipid oxidation [15]. In order to improve our knowledge about the effects of ethanol on Se bioavailability in pups, we will study duodenal Se absorption.…”
supporting
confidence: 69%
“…We have previously found that, as a direct effect of ethanol exposure, an imbalance on Se homeostasis occurs and that there is a de-pletion of this element in different tissues in pups [15]. To increase our knowledge about Se bioavailability after ethanol exposure, we have studied duodenal Se absorption.…”
Section: Duodenal Absorption Of Selenomethioninementioning
confidence: 99%
“…The results of this study showed a 30 % decline in the weight of suckling rats and a decrease in growth indices (biparietal diameter and crown-rump Length) in the group on 4 % v/v ethanol compared to the control group. This could be directly related to the quality and quantity of milk produced by the dam, because consumption of ethanol during pregnancy and lactation can cause changes in macronutrients and micronutrients (Azara et al 2008) and antioxidants of milk ingredients (Ojeda et al 2009). Numerous studies have shown ethanol-induced reduction in milk production during breastfeeding, and severe malnutrition and adverse effects in neonates hence result in reduction in sucking by neonates which has an effect on the release of dam's oxytocin and prolactin (Subramanian 1995;Tavares 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Die Verminderung des mittleren Selenspiegels bei regelmäßigem Alkoholkonsum wurde bereits in verschieden klinischen und experimentellen Settings untersucht [27,28].…”
Section: Demand For and Clinical Practice Of Complementary Selenium Tunclassified